410. Characteristics of Patients with Extended-Spectrum Beta-Lactamase (ESBL) Producing Enterobacterales, Tennessee, 2019-2020. (15th December 2022) - Hitchingham, Erin; Muleta, Daniel; Villegas, Raquel; Gambrell, Ashley; Bailey, Cherlly; Wilson, Christopher; Mounsey, Jackie
Abstract: Background: Currently, data on the incidence of Enterobacterales bacteria that produce extended-spectrum beta-lactamases (ESBL) within community settings is lacking. We set out to describe patient characteristics for healthcare-associated (HA) and community-associated (CA) ESBL-producing Enterobacterales in Tennessee. Methods: ESBL cases were defined as isolation of Escherichia coli, Klebsiella pneumoniae, or Klebsiella oxytoca, resistant to cefotaxime, ceftriaxone, or ceftazidime, non-resistant to all tested carbapenems, from a normally sterile body site, or urine, within Maury, Lewis, Marshall, or Wayne Counties, with a specimen collection date from July 1 st, 2019, to the end of 2020. Patient data was collected by reviewing patients' medical records. HA cases were defined as those with previous healthcare exposures, of any kind, in the year preceding specimen collection. All analysis was performed using SAS 9.4. Results: 566 cases were included in this study. Demographically, 459 (81.1%) cases identified as white with an equal number (81.1%) of patients being female. The average age was 66.2 years. 560 (98.94%) specimens were collected from urine, 468 (85.1%) patients had a urinary tract infection (UTI), and 174 (37.2%) of those patients had a record of recurrent UTIs. 243 (49.6%) cases were identified as CA. 138 (24.4%) cases were identified as being hospitalized within 29 days of their specimen collection and 247 (50.4%) cases were determined to be HA. 142 (25.1%) patients were treated with antibiotic in the month before specimen collection. Cephalosporins (31.7%), fluroquinolones (29.6%), doxycycline (7.7%), and sulfonamides (7.7%) were the most common antibiotics used to treat the patients. Among patients prescribed these antibiotics (N=109), 19 (17.4%) patients had specimens resistant. Figure 1: Characteristics of patients with extended-spectrum beta-lactamases (ESBL) producing Enterobacterales isolated from 2019-2020 Figure 2: Characteristics of patients with extended-spectrum beta-lactamases (ESBL) producing Enterobacterales isolated from 2019-2020, continued Conclusion: Most cases were described in white women with UTIs, often recurrent, coming from private residences. With approximately 50% of cases described as CA, targeted intervention outside of healthcare facilities is necessary to reduce spread of ESBL infections. As 17.4% of cases were treated with antibiotics that the organism was resistant, there is an opportunity to improve judicial use of antibiotics based on susceptibility data. Disclosures: All Authors : No reported disclosures.